2022
DOI: 10.3389/fcvm.2022.941434
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Very High-Power, Short-Duration Radiofrequency Applications

Abstract: IntroductionPulmonary vein isolation is the cornerstone of rhythm-control therapy for atrial fibrillation (AF). The very high-power, short-duration (vHPSD) radiofrequency (RF) ablation is a novel technology that favors resistive heating while decreasing the role of conductive heating. Our study aimed to evaluate the correlations between contact force (CF), power, impedance drop (ID), and temperature; and to assess their role in lesion formation with the vHPSD technique.MethodsConsecutive patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
1
9
1
Order By: Relevance
“…The present study demonstrated that steam‐pops were observed in 4.4% of SA approach. However, clinical trials of 90 W/4 s ablation using the QDOT‐MICRO™ catheter described a lower rate of steam‐pops (=0%) than in this study 3,9,14,18 . In the present un‐perfused ex vivo model without cardiac and respiratory movement, steam‐pop risks might be overestimated, 19 and lesion characteristics might be different from those in a clinical setting.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The present study demonstrated that steam‐pops were observed in 4.4% of SA approach. However, clinical trials of 90 W/4 s ablation using the QDOT‐MICRO™ catheter described a lower rate of steam‐pops (=0%) than in this study 3,9,14,18 . In the present un‐perfused ex vivo model without cardiac and respiratory movement, steam‐pop risks might be overestimated, 19 and lesion characteristics might be different from those in a clinical setting.…”
Section: Discussioncontrasting
confidence: 69%
“…However, clinical trials of 90 W/4 s ablation using the QDOT-MICRO™ catheter described a lower rate of steam-pops (=0%) than in this study. 3,9,14,18 In the present un-perfused ex vivo model without cardiac and respiratory movement, steam-pop risks might be overestimated, 19 and lesion characteristics might be different from those in a clinical setting. In the present study, the number of steam-pops was relatively low especially for SAs.…”
Section: Limitationsmentioning
confidence: 77%
“…The vHPSD strategy aims to create shallower but wider lesions in a very short time by reducing conductive heating and increasing resistive heating at the same time. Additionally, collateral tissue damage might be reduced 28,31 …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Recently, a very HPSD (vHPSD; 90 W, 4 s) technique has been introduced, but initial efficacy results were mostly discouraging regarding first-pass isolation rates, acute reconnection rates, and arrhythmia-free survival. [10][11][12][13][14] We hypothesized that vHPSD PVI could result in similar acute and long-term efficacy as ablation indexguided PVI with 50 W. 11 Therefore, we designed the HPSD Remap study (Efficacy Comparison of High and Very High Power Short Duration Pulmonary Vein Isolation, URL: https://www.clinicaltrials.gov; unique identifier NCT05459831), in which durability of lesions was assessed by a repeat electrophysiology study after an index PVI performed with either a 90-or 50-W power setting.…”
mentioning
confidence: 99%
“…5–9 Recently, a very HPSD (vHPSD; 90 W, 4 s) technique has been introduced, but initial efficacy results were mostly discouraging regarding first-pass isolation rates, acute reconnection rates, and arrhythmia-free survival. 10–14…”
mentioning
confidence: 99%